Kapitalisme Pendidikan di Sekolah Satuan Pendidikan Kerjasama (SPK) dalam Perspektif Teori Keadilan (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
In practice, the Cooperative Education Unit (SPK) does not provide the same space for every Indonesian citizen to get a quality education. SPK has becomea practice of educational capitalism that further widens the gap between one person and another and eliminates the principle of justice where everyone has the right to equal opportunities for education. The method used in this study is normative legal research that uses three approaches, namely the legislative approach, the case approach, andthe conceptual approach. With the analysis using the perspective of critical law and the theory of Justice John Rawls. The result of this study is a policy recommendation so that the Cooperative Education Unit (SPK) school policy as a product of government policy in the education area contained in Permendikbud No. 31 of 2024 should be reviewed, corrected and returned to be a policy in accordance with national education goals. In order to be in line with the constitutional mandate to educate the life of the nation and to provide space or access to every citizen to get his or her constitutional right to education.